Error Analysis of English Abstract in International Journal of Economics, Business and Accounting Research (IJEBAR) - Tira Nur Fitria (LP2M IAIN Sultan Amai Gorontalo, 2020)
This study aims to determine the types of errors and the most dominant type of errors in the International Journal of Economics, Business, and Accounting Research (IJEBAR) STIE AAS Surakarta, published in 2018. This study employed a qualitative method. The author used documents to collect data and analyzed the data by identifying errors, classifying errors, explanation errors, and tabulating errors. The research findings showed that the type of errors in IJEBAR was related to some aspects of writing, such as grammar, punctuation, and spelling. In the grammar aspect, there were 36 data or 50.70 %, which consist of some errors in class words (part of speech), for example in determiner/article (22 data or 61.11 %), verb (11 data or 30.56 %), preposition (2 data or 5.56 %), and noun (1 data or 2.78 %). There were 21 data or 29.58 % in the punctuation aspect, and in the spelling aspect, there are 14 data or 19.72 %. The most dominant type of errors found in IJEBAR is the aspect of grammar, as 36 data or 50.70%. Errors can be caused by a lack of language skills such as the learner's lack of knowledge of the target language's correct rules or an error in translating using specific translation tools. Therefore, in writing English abstract well and correctly, it should follow the language (English) rule, which refers to the correct grammatical, punctuation, and spelling aspect.